The effect of beetroot supplement on sprinting performance / Maisarah Mohd Saleh, Saidatul Nur Syuhadah Mohamed Sabadri and Nur Farhana Mohd Nasir - Mohd Saleh, Maisarah; Mohamed Sabadri, Saidatul Nur Syuhadah; Mohd Nasir, Nur Farhana (Universiti Teknologi MARA, 2020)
The consumption of beetroot supplementation has increased the popularity of studies that showed the ergogenic effects on exercise performance. Since beetroot juice supplement can enhance physiological processes in type II (fast twitch) muscle fiber, this supplementation has the potential to enhance performance in high intensity exercise which is sprinting. The purpose of this study is to determine the effect of beetroot supplement on sprint performance. Using a double blind, crossover design this study recruited 12 male sprinters from SMK Dato Sri Amar Diraja to measure their sprint performance in 30- meter sprint test. Data analyzed using paired sample t-Test. From the results, it showed no significant effects of beetroot supplement on sprinting performance were observed between beetroot and placebo group. The results were due to the lack of dose ingested showed no ergogenic effects of beetroot supplement on sprinting performance.